An Importance of Magnesium Deficiency in the Formation of Vegetative Disadaptation in Children and Adolescents with Digestive Tract Pathology - L. M.Boiarska; S. V. Gorbachova; S. V. Potapenko (Zaporožskij Medicinskij Žurnal)
Aim. In the study of magnesium deficiency, a distinction is made between magnesium hypoelementosis and magnesium deficit. As a result, detection of the magnesium deficiency and its influence on vegetative disadaptation progression can help to correct damages in early stages and to decrease frequency of chronization of digestive tract disorders in children.